Spiritual economies : female monasticism in later medieval England - Warren, Nancy Bradley (Middle Ages series., 2001)
"From its creation in the early fourteenth century to its dissolution in the sixteenth, the nunnery at Dartford was among the richest in England. Although obliged to support not only its own community but also a priory of Dominican friars at King's Langley, Dartford prospered. Records attest to the business skill of the Dartford nuns, as they managed the house's numerous holdings of land and property, together with the rents and services owed them. That the Dartford nuns were capable businesswomen is not surprising, since the house was also a center of female education." "For Nancy Bradley Warten, the story of Dartford exemplifies the vibrancy of nuns' material and spiritual lives in later medieval England. Revising the long-held view that fourteenth- and fifteenth-century English nunneries were impoverished both financially and religiously, Warren clarifies that the women in female monastic communities like Dartford were not woefully incompetent at managing their affairs. Instead, she reveals the complex role of female monasticism in diverse systems of production and exchange. Like the nuns at Dartford, women religious in late medieval England were enmeshed in material, symbolic, political, and spiritual economies that were at times in harmony and at other times in conflict with each other."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.